2008
DOI: 10.1111/j.1365-2761.2008.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of rainbow trout, Oncorhynchus mykiss (Walbaum), with a low molecular mass fraction isolated from Flavobacterium psychrophilum

Abstract: Flavobacterium psychrophilum, the causative agent of rainbow trout fry syndrome has become a widespread fish pathogen in freshwater aquaculture worldwide. In this study, a low molecular mass fraction (P25-33), with an approximate weight of 25-33 kDa, was identified among F. psychrophilum strains in an immunoblotting analysis with anti-F. psychrophilum sera. The immunogenic efficacy of the isolated and extracted P25-33 was investigated in two intraperitoneal immunization trials with rainbow trout, Oncorhynchus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Previous studies using inactivated F. psychrophilum in conjunction with oil adjuvants have demonstrated protection, usually associated with increased levels of specific IgM in the serum of vaccinated fish (Fredriksen et al, 2013;Hoare, Jung, et al, 2017;Högfors, Pullinen, Madetoja, & Wiklund, 2008;Madetoja et al, 2006). The protection in the current study appears to be at least partly mediated by specific serum antibodies Previous studies have identified different molecular weight fractions (18-28, 41-49 and 70-100 kDa) as immunogenic molecules of F. psychrophilum by Western blotting, using convalescent rainbow trout serum (Crump, Perry, Clouthier, & Kay, 2001;Högfors et al, 2008;LaFrentz, Lindstrom, LaPatra, Call, & Cain, 2007).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies using inactivated F. psychrophilum in conjunction with oil adjuvants have demonstrated protection, usually associated with increased levels of specific IgM in the serum of vaccinated fish (Fredriksen et al, 2013;Hoare, Jung, et al, 2017;Högfors, Pullinen, Madetoja, & Wiklund, 2008;Madetoja et al, 2006). The protection in the current study appears to be at least partly mediated by specific serum antibodies Previous studies have identified different molecular weight fractions (18-28, 41-49 and 70-100 kDa) as immunogenic molecules of F. psychrophilum by Western blotting, using convalescent rainbow trout serum (Crump, Perry, Clouthier, & Kay, 2001;Högfors et al, 2008;LaFrentz, Lindstrom, LaPatra, Call, & Cain, 2007).…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies using inactivated F. psychrophilum in conjunction with oil adjuvants have demonstrated protection, usually associated with increased levels of specific IgM in the serum of vaccinated fish (Fredriksen et al., ; Hoare, Jung, et al., ; Hoare, Ngo, et al., ; Högfors, Pullinen, Madetoja, & Wiklund, ; Madetoja et al., ). The protection in the current study appears to be at least partly mediated by specific serum antibodies (IgM) as shown by ELISA, agglutination and Western blotting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth phase of the bacterial challenge culture could also affect the virulence [4] as could the number of passages on artificial medium (authors' own observation). Challenge by intraperitoneal, subcutaneous or intramuscular injection [2,5,7] fish, including the protective immune mechanisms of the skin and may therefore not be appropriate for evaluation of immersion vaccines [7,13]. To address this matter, the present study aimed at investigating whether immersion in high titres of wildtype isolates of F. psychrophilum would be able to stimulate a systemic immune response conferring protection against a subsequent ip challenge.…”
Section: Introductionmentioning
confidence: 97%
“…Vaccination by intraperitoneal (ip) injection of heat inactivated, formalin killed, or sonicated cells or subunit vaccines, with or without use of adjuvant, may confer good protection [1,2,5,8], but ip vaccination is not realistic for small fry. The fry have to be vaccinated as early as possible, as RTFS can cause problems soon after start of feeding, when the fish are only around 0.2e0.5 g. For salmonids, the minimum size of onset of an economically acceptable level of adaptive immunity is from 0.5 to 2.5 g by use of inactivated bacterial immersion vaccines of Yersinia ruckeri and Vibrio anguillarum [9e11].…”
Section: Introductionmentioning
confidence: 99%